2021
DOI: 10.1155/2021/2396008
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analgesic Effects of Different κ‐Receptor Agonists Used in Daytime Laparoscopic Cholecystectomy

Abstract: Background. Comparing the effect of two different κ-receptor agonists, nalbuphine and oxycodone, and regular morphine in patients for prophylactic analgesia of acute pain after daytime laparoscopic cholecystectomy. Methods. One hundred and twenty-four patients undergoing laparoscopic cholecystectomy were randomly allocated to receive nalbuphine (group N), oxycodone (group O), and morphine (group M). The three groups were all given intravenous injection (iv.) of 0.15 mg/kg injection before incision and 0.05 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Visceral pain is a large contributor of postoperative pain in patients with laparoscopic surgery for gastrointestinal cancer (4,12,13). κ-opioid receptor plays an important role in the mediation of visceral pain (6). Oxycodone, a dual agonist of μ and κ receptors (14), has been shown to provide effective analgesia for acute postoperative pain (15,16), especially visceral pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visceral pain is a large contributor of postoperative pain in patients with laparoscopic surgery for gastrointestinal cancer (4,12,13). κ-opioid receptor plays an important role in the mediation of visceral pain (6). Oxycodone, a dual agonist of μ and κ receptors (14), has been shown to provide effective analgesia for acute postoperative pain (15,16), especially visceral pain.…”
Section: Discussionmentioning
confidence: 99%
“…Although PCIA has been applied, some patients still experienced visceral pain following abdominal surgery (5). Considering κ-opioid receptor has been found to be involved in visceral pain (6), it is possible that both μ and κ-opioid receptors agonist, such as oxycodone, may provide more effective analgesia than pure μ-opioid receptor agonist in patients following laparoscopic surgery for gastrointestinal cancer (4,7). However, oxycodone in PCIA may cause serious side effects, including respiratory depression, apnea, bradycardia, hypotension, or even death (8).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%